Causes and Effects of Oocyte Retrieval Difficulties: A Retrospective Study of 10,624 Cycles - Wang, Yang; Zhang, Meixiang; Shi, Hao; Yi, Shiqi; Li, Qian; Su, Yingchun; Guo, Yihong; Hu, Linli; Sun, Jing; Sun, Ying-pu (Frontiers in Endocrinology, 2022)
Oocyte retrieval is a routine procedure during the application of assisted reproduction technology. However, technical difficulties experienced during oocyte retrieval and the subsequent unsatisfactory number of oocytes obtained are rarely reported. The current study included 10,624 oocyte retrieval cycles from April 2015 to June 2018, and patients were followed up until February 2019. Patients were divided into two groups depending on whether the oocyte number obtained reached the > 14mm follicle number on the day of hCG administration. In the oocyte retrieval not satisfactory (ORNS) group there were 1294 cycles, and in the oocyte retrieval satisfactory (ORS) group there were 9330 cycles. ORNS patients were older, had a longer duration of infertility, had higher follicle-stimulating hormone, and were more likely to have endometriosis. The ORS group had a higher rate of the use of a follicular phase long-acting gonadotropin-releasing hormone (GnRH) agonist long ovarian stimulation protocol, and a lower rate of the use of a luteal phase short acting GnRH agonist long protocol. The ORNS group had fewer total number of days of FSH stimulation. On human chorionic gonadotropin day, the ORNS group had higher luteinizing hormone (LH), lower estradiol, and lower progesterone levels. After oocyte retrieval, the oocyte quality and fresh cycle transplantation rate were higher in the ORNS group. An unsatisfactory oocyte retrieval number did not influence the clinical pregnancy rate, miscarriage rate, or live birth rate during fresh cycles. The cumulative pregnancy rate and the live birth rate were lower in the ORNS group. In conclusion, with a similar number of matured follicles, ORNS was more likely to occur in ovarian dysfunction patients. The follicular phase long-acting GnRH agonist long protocol had lower oocyte retrieval difficulty during IVF/ICSI. ORNS does not affect embryo quality or the fresh cycle pregnancy rate, but it significantly reduces the cumulative pregnancy rate and the live birth rate.